Does wound infi ltration of tramadol reduce postoperative pain in laparoscopic or open herniorrhaphy? - Remziye Sıvacı; Erol Eroglu; Lutfi Yavuz; Fusun Eroglu; Yaşar Sıvacı (Journal of Health Sciences, 2012)
Introduction: The laparoscopic approach may be associated with more postoperative pain initially. The aim of this study was to evaluate the effects of administered tramadol at wound closure on postoperative pain and analgesic requirements under spinal anesthesia in laparoscopic inguinal herniorrhaphy (LH) or tension free open inguinal herniorrhaphy (TFOH). Methods: Twenty patients were randomly divided into two groups (n= 10 in each) as LH or TFOH. Patients received infiltration of 200 mg tramadol with 40 mL of 0.9% saline solution at wound closure procedure. Postoperative pain was assessed with a Visual Analog Scale (VAS) at 3, 6, 12, and 24 hours postoperatively. Additional requirements of tramadol for postoperative pain releif were registered. Results: VAS scores at postoperative 12 and 24 hours were signifi cantly higher according to 3rd hour VAS scores in both groups. The VAS scores at 12 hours after operation signifi cantly lower in LH group than in TFOH group (1.5 ± 0.97 vs 5.1 ± 0.99). Additional requirements of tramadol for postoperative pain releif were significantly lower in LH group. Conclusion: We conclude that wound infi ltration of 200 mg tramadol reduce postoperative pain in LH group.